Preventing lithium ion battery failure during high temperatures by externally applied compression - Zhao,Y; Patel,Y; Hunt,IA; Kareh,KM; Holland,AA; Korte,C; Dear,JP; Yan,Y; Offer,GJ (Journal of Energy Storage, 2017)
Lithium-ion cells can unintentionally be exposed to temperatures outside manufacturers recommended limits without triggering a full thermal runaway event. The question addressed in this paper is: Are these cells still safe to use? In this study, externally applied compression has been employed to prevent lithium ion battery failure during such events. Commercially available cells with Nickel Cobalt Manganese (NCM) cathodes were exposed to temperatures at 80 °C, 90 °C and 100 °C for 10 h, and electrochemically characterised before and after heating. The electrode stack structures were also examined using x-ray computed tomography (CT), and post-mortems were conducted to examine the electrode stack structure and surface changes. The results show that compression reduces capacity loss by −0.07%, 4.95% and 13.10% respectively, measured immediately after the thermal testing. The uncompressed cells at 80 °C showed no swelling, whilst 90 °C and 100 °C showed significant swelling. The X-ray CT showed that the uncompressed cell at 100 °C suffered de-lamination at multiple locations after test, and precipitations were found on the electrode surface. The post-mortem results indicates the compressed cell at 100 °C was kept tightly packed, and the electrode surface was uniform. The conclusion is that externally applied compression reduces delamination due to gas generation during high temperature excursions.